Quantum Entanglement and Its Classification Protocols - Amirul Asyraf Zhahir; Siti Munirah Mohd; Mohd Sham Mohamad; Mohd Ilias M Shuhud; Bahari Idrus; Hishamuddin Zainuddin; Nurhidaya Mohamad Jan (Universiti Sains Islam Malaysia, 2024)
Malaysian Journal of Science Health & Technology, Volume 10 issue 2 Page (99–106)